2018
DOI: 10.1177/1461444818775698
|View full text |Cite
|
Sign up to set email alerts
|

Online volunteering as a means to overcome unequal participation? The profiles of online and offline volunteers compared

Abstract: A key question regarding the ongoing process of digitalization is whether it enables societies to overcome patterns of inequality or whether these patterns are fostered in the digital sphere. The article addresses this question for the case of online volunteering by examining the profiles of online and offline volunteers in terms of sociodemographics, resources, networks, and psychological engagement. We apply quantitative methods using a unique data set that provides comprehensive information on online volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 38 publications
(54 reference statements)
1
36
0
Order By: Relevance
“…We have shown in this study that online volunteering is a great tool for humanitarian programs. Online volunteering and using online tools for voluntary work is widespread in different elds including heritage, health, disaster preparedness, emergency response, learning language, and sport [19][20][21][22][23]. Our study indicates that beside usual volunteers, there are opportunities for refugees, women, and citizens in other provinces and countries to participate virtually in humanitarian activities.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have shown in this study that online volunteering is a great tool for humanitarian programs. Online volunteering and using online tools for voluntary work is widespread in different elds including heritage, health, disaster preparedness, emergency response, learning language, and sport [19][20][21][22][23]. Our study indicates that beside usual volunteers, there are opportunities for refugees, women, and citizens in other provinces and countries to participate virtually in humanitarian activities.…”
Section: Discussionmentioning
confidence: 81%
“…For example, Atkins and Thompson (2012) introduced six potential groups of which talented online volunteers may be recruited including volunteers facing geographic constraints, skilled immigrants, stay-at-home parents, retirees, individuals with physical limitations, and young adults [24]. Various studies have indicated that online volunteering is a way to reduce inequality in volunteering participation [20,25]. However, it should be noted that refugees and minority groups may have less access to cyberspace infrastructures such as personal computers and smartphones [26].…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of virtual volunteering, however, is more recent (Ihm, 2017 ), and while the COVID-19 pandemic triggered a host of virtual volunteering initiatives (Carlsen, Toubøl, and Brincker 2020 ), the field of online volunteer research remains in its infancy (Eimhjellen, 2019 ). At present, the literature is dominated by descriptive and exploratory studies that demarcate and map the field (Ackermann and Manatschal 2018 ; Mukherjee, 2011 ), supply advice to managers of virtual volunteers (Cravens, 2000 ; Dhebar & Stokes, 2008 ), or map the motivations and characteristics of volunteers (Eimhjellen, 2019 ). Consequently, questions such as how ICT impacts intra-organizational sensemaking and inequality in voluntary interaction demand further examination (Carlsen, Doerr, and Toubøl 2020 ).…”
Section: The Pursuit Of Intimacy and The Production Of Inequality In mentioning
confidence: 99%
“…In contrast, retention efforts must promote increased social connections, ensuring organizations have nondiscrimination policies, use affirming language, and promote an inclusionary organizational culture (Gates & Lillie, 2020). Future research should also examine emerging forms of volunteerism, including virtual or e-volunteerism (Ackermann & Manatschal, 2018) and its potential impact upon LGBTQ+ well-being.…”
Section: Implications and Future Directions For Mental Health And Volmentioning
confidence: 99%